Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1148/radiology.170.2.2911674
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function, and degeneration of bovine hyaline cartilage: assessment with MR imaging in vitro.

Abstract: The basic magnetic resonance (MR) imaging pattern of normal and degenerated hyaline articular cartilage was studied in vitro in 40 fresh bovine patellae. With the use of an ample spectrum of strongly T1- to T2-weighted sequences, two zones of cartilage with different signal intensities were observed in all specimens. A superficial cartilaginous layer in the MR image with higher water content and longer T1 and T2 correlated with the tangential and transitional zones of normal articular cartilage, whereas a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(95 citation statements)
references
References 0 publications
5
88
1
1
Order By: Relevance
“…These relaxation values confirm the dominant effect of the administered gadolinium, since the T1 relaxation value without gad- olinium is reported in the literature to be around 770 msec (15). For T2, our reported T2 relaxation values (with a mean T2 relaxation value of 34 msec) apparently are lower than those found in the literature (2,3,12,16,17). However, these results should be interpreted in the light of a recent study by Goodwin et al (17), in which they evaluated the relationship between T2 relaxation values and the cartilage matrix architecture.…”
Section: Discussionsupporting
confidence: 87%
“…These relaxation values confirm the dominant effect of the administered gadolinium, since the T1 relaxation value without gad- olinium is reported in the literature to be around 770 msec (15). For T2, our reported T2 relaxation values (with a mean T2 relaxation value of 34 msec) apparently are lower than those found in the literature (2,3,12,16,17). However, these results should be interpreted in the light of a recent study by Goodwin et al (17), in which they evaluated the relationship between T2 relaxation values and the cartilage matrix architecture.…”
Section: Discussionsupporting
confidence: 87%
“…Most studies have also found that the effect of proteoglycans on T 2 is negligible [26,28,50,78,80]. T 2 varies through the depth of articular cartilage, reflecting the depth-dependent content and structure of the collagen matrix (figure 3c), with T 2 increasing from deep to superficial tangential zones [26,29,30,33,81]. T 2 -weighted images can also been used to assess water content in cartilage [15,16].…”
Section: T 2 Mappingmentioning
confidence: 99%
“…9). Studies demonstrating the variation of T 2 across cartilage were first published in 1989 (171). Since then, numerous reports delineate the decreased T 2 in areas where collagen is highly structured (deep zone) [e.g.…”
Section: Quantitative Measurements Of Cartilage Composition In Oamentioning
confidence: 99%